Application of Franchising as a Form of Agreement Object - Clarissa Aurelia Susanto; Urbaniasi Urbaniasi (CV. Rayyan Dwi Bharata, 2023)
The approach in this study uses a normative juridical approach. The juridical approach is an approach to the problem by looking at it from the point of view of the applicable laws and regulations, especially regarding the application of franchising as a form of agreement. Therefore, this type of research is normative relating to the principles and norms in the implementation of franchise agreements, namely between the franchisor and the franchisee. In this paper using primary and secondary data obtained from library materials in the form of laws, government regulations, the Civil Code and literature related to problems and derived from legal materials such as primary legal materials, secondary legal materials and tertiary legal materials. A franchise agreement is a form of agreement involving the franchisor as the franchisor and the franchisee receiving the franchise. This legal relationship gives rise to binding rights and obligations for franchisors and franchisees. The franchise agreement includes an innominate agreement that is regulated outside the Criminal Code. Legal sanctions in violation of franchise agreements are regulated in Article 16 of Government Regulation Number 42 of 2007 where legal sanctions in the form of administrative sanctions are carried out through 3 (three) stages, namely giving written warnings, fines and/or revocation of franchise registration certificates.